Pendidikan sebagai Investasi Modal SDM: Analisis Nilai, Dampak Sosial-Ekonomi - Siti Maesaroh; Sita Ratnaningsih; Nurochim Nurochim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Education is widely recognized as a key driver of human capital formation, yet many studies still treat its economic and social impacts in a fragmented manner. This article addresses that gap by providing an integrated review of how education functions as a long-term investment that strengthens skills, productivity, and social well being. The study aims to examine the value of education as human capital investment and to synthesize its socio-economic impacts based on recent empirical findings. Using a structured literature review, data were gathered from national and international journal articles published between 2015-2024, selected through relevance, credibility, and thematic alignment with human capital theory. The analysis shows that investment in education consistently enhances individual productivity, widens employment opportunities, and increases lifetime earnings. At the macro level, higher educational attainment contributes to economic growth through better utilization of labor quality, increased innovation capacity, and improved social cohesion. The review also highlights that education reduces unemployment risks, supports poverty alleviation, and strengthens community welfare. These findings reaffirm that education serves not only as a social responsibility but also as a strategic economic instrument that generates long-term returns for individuals and the state.